2014
DOI: 10.1016/j.lingua.2014.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Subject inversion in non-native Spanish

Abstract: This study presents new empirical evidence on the L2 acquisition of Spanish SV-VS contrasts, a syntax-pragmatics interface phenomenon. Results from a context-dependant preference task involving unergative and unaccusative verbs in different focus situations (broad and narrow focus) reveal that beginner and intermediate English speakers prefer SV in all contexts. In contrast, advanced learners, who clearly know that VS is possible in Spanish, show a pattern of optionality with unergative verbs (in both broad an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 54 publications
(70 reference statements)
2
28
1
2
Order By: Relevance
“…A further result of this study concerns the classification of verbs themselves. Unlike previous empirical studies (Hertel, 2003 ; Lozano, 2006a , b ) and contra the theoretical literature (Contreras, 1978 ; Suñer, 1982 and Zubizarreta, 1998 ), the data revealed no clear-cut across-the-board binary distinction between unergatives and unaccusatives (but see Domínguez and Arche, 2014 ). Neither monolinguals nor bilinguals differentiated the two types of verbs in non-focus situations.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…A further result of this study concerns the classification of verbs themselves. Unlike previous empirical studies (Hertel, 2003 ; Lozano, 2006a , b ) and contra the theoretical literature (Contreras, 1978 ; Suñer, 1982 and Zubizarreta, 1998 ), the data revealed no clear-cut across-the-board binary distinction between unergatives and unaccusatives (but see Domínguez and Arche, 2014 ). Neither monolinguals nor bilinguals differentiated the two types of verbs in non-focus situations.…”
Section: Discussioncontrasting
confidence: 89%
“…Ocampo ( 1990 ) and Camacho ( 1999 ) similarly reported that the acquisition of distinct word orders to mark focus in Spanish is acquired late or perhaps never in native-like fashion. More recently, Domínguez and Arche ( 2014 ) argued after looking at their native data that the linguistic evidence available for acquiring the syntactic properties of unergative and unaccusative verbs in Spanish is not completely transparent and that L2 speakers may not get clear evidence, which can explain why learners find the acquisition of SV–VS contrasts persistently difficult. However, they claim that their analysis is compatible with the view that L2 speakers eventually converge on the grammar of native speakers, and that this may well be the case with their advanced speakers as their experience in the L2 increases.…”
Section: Theoretical Background: Is Word Order At the Interfaces Acqumentioning
confidence: 99%
See 1 more Smart Citation
“…For Spanish, some evidence suggests that focus is acquired late and/or exhibits protracted optionality for L2 learners, as the IH predicts (Hertel, 2003;Lozano, 2006aLozano, , 2006b). However, other evidence indicates that learners can eventually acquire discourse-related word order alterations, with targetlike performance on information-structural categories at advanced proficiency levels (Domínguez & Arche, 2008, 2014Hertel, 2003;Leal Méndez & Slabakova, 2011;Slabakova, Kempchinsky, & Rothman, 2012;Slabakova, Rothman, & Kempchinsky, 2011).…”
Section: Heritage Spanish and The Syntax-discourse Interfacementioning
confidence: 99%
“…This pitch accent consists of a low tone at the beginning of the stressed syllable in the accented word that rises to a high tone within the same syllable. It is one of the pitch accents most commonly used to mark main sentence stress on focused constituents in Spanish (Face, 2003;Henriksen, 2011;Kim & Avelino, 2003). Although more than one pitch accent in Spanish can be associated with sentence stress, one pitch accent was chosen in order to control for the perception 4.…”
Section: Stimulimentioning
confidence: 99%